Result catamnesis of the treatment of patients with acute Lyme mite borreliosis - M. N. Dobkina; A. V. Lepyekhin; N. G. Zhukova; L. V. Lukashova; G. N. Zaviyalova; T. A. Kiyutsina (Бюллетень сибирской медицины, 2003)
The aim of the work is to study the efficiency of different antibacterial medication combinations for the treatment of patients with acute Lyme mite borreliosis. 156 patients aged 20—76 have been on regular medical check-up. Different penicillin and tetracycline antibiotics have been applied as well as cephalosporins of 1 and 3 generation. The treatment duration has been 7—14 days. The duration of general intoxication syndrome, terms of clinical symptom dissapearance, antibody titer dynamics in indirect immunofluorescence reaction with borreliosis antigen, presence of side actions and long-term results of the treatment have been taken into account in the evaluation of different antibiotic combination efficiency. 1 year after discharge from the hospital 69,2% of observed persons considered themselves healthy, 15,4% obtained the diagnosis of chronic clinical LMB with predominant joint or nervous system damages. Thus, analysis of the investigation result shows that currently used etiotropic therapy regimens are not sufficiently effective. They allow recovery of 69,2% of patients with acute Lyme mite borreliosis only.